(untitled) (Comprehensive Journal of Science, 2026)
This study aims to analyze the impact of money supply and government expenditure shocks on inflation rates in Libya over the period 1990-2023. The analysis employs impulse response functions and forecast error variance decomposition, in addition to Granger causality tests. The results indicate that both money supply and government expenditure have positive effect on inflation; however, the impact of money supply is stronger and more persistent, particularly over the medium and long run. The variance decomposition analysis further shows that money supply explains the largest proportion of inflation fluctuations, whereas the effect of government expenditure remains relatively limited. In the short run, inflation is largely driven by its own shocks. Moreover, the Granger causality tests confirm the existence of a causal relationship running from money supply to inflation. The study recommends strengthening the role of monetary policy and improving its coordination with fiscal policy.